Effectiveness of Memorizing Juz Amma Santri TPQ Nurul Qur'an with Reward Strategy - Ucik Nurul Hidayati; Sinta Putri Dewi; Zuli Dwi Rahmawati (Sustainable, 2023)
A reward is a method used by someone to give someone appreciation for having done something right, so that someone can be more enthusiastic in doing certain tasks and more motivated in doing other things and the process is better so that someone is able to achieve the success of something he does. This research discusses giving rewards to students given by their ustadzah ustadz to reward them for what they have achieved. In its application, ustadzah ustadz can give rewards in the form of words, praise, goods, pins, grades or other things. Rewards or awards given to students can increase their self-confidence, foster motivation to learn, and develop themselves. Practically speaking, appreciation means an act of appreciation or respect. Rewards can also be called rewards that are like gifts.